2014
DOI: 10.1134/s1022795414110027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms of genes associated with immune response and tissue remodeling in occupational chronic bronchitis

Abstract: The involvement of polymorphisms of genes encoding immune response associated molecules (LTA, TNFA, IL1B, ILRN, IL8, IL10, VDBP), matrix metalloproteinases (MMP1, MMP2, MMP3, MMP9, MMP12, ADAM33), and tissue and serum inhibitors of metalloproteinases (TIMP2, TIMP3, SERPINA1, SERPINA3) in the predisposition to occupational chronic bronchitis was assessed by PCR-RFLP analysis in groups of patients (n = 122) and healthy workers (n = 166). It was found that occupational chronic bron chitis was associated with poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For instance, SERPINA3 is one of the proteins in signal transduction pathways of the inflammatory response. A study of clinical relapsed ovarian tumors showed that the up-regulation of SERPINA3 was associated with disease progression and chemical resistance[16]. Moreover, another study showed that methylation of the 5' region may account for up-regulation of SERPINA3 in placental disease.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SERPINA3 is one of the proteins in signal transduction pathways of the inflammatory response. A study of clinical relapsed ovarian tumors showed that the up-regulation of SERPINA3 was associated with disease progression and chemical resistance[16]. Moreover, another study showed that methylation of the 5' region may account for up-regulation of SERPINA3 in placental disease.…”
Section: Discussionmentioning
confidence: 99%
“…Declining of proliferation and increasing the apoptosis of ASMCs in a rat model of allergic asthma can be caused by silencing of ADAM33 (20) . The genetic susceptibility to patients who get chronic bronchitis caused by smoking or aerosols and industrial dust can be enhanced by ADAM33 gene polymorphisms (21) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rs1799750 in MMP1 was identified as associated with the mainly apical densitometric distribution of emphysema 124 , while the carriers of allele T of rs470358 are associated with the transference of gases in patients with COPD secondary to AATd 125 . Finally, polymorphisms in MMP1 have also been associated with the predisposition to occupational chronic bronchitis 126 .…”
Section: Genes Of Extracellular Mmps and Copdmentioning
confidence: 99%